From Clinging to Digging: The Postembryonic Skeletal Ontogeny of the Indian Purple Frog, Nasikabatrachus sahyadrensis (Anura: Nasikabatrachidae) - Senevirathne, Gayani; Thomas, Ashish; Kerney, Ryan; Hanken, James; Biju, S. D.; Meegaskumbura, Madhava (PLOS ONE, 2016)
The Indian Purple frog, Nasikabatrachus sahyadrensis, occupies a basal phylogenetic position among neobatrachian anurans and has a very unusual life history. Tadpoles have a large ventral oral sucker, which they use to cling to rocks in torrents, whereas metamorphs possess adaptations for life underground. The developmental changes that underlie these shifts in habits and habitats, and especially the internal remodeling of the cranial and postcranial skeleton, are unknown. Using a nearly complete metamorphic series from free-living larva to metamorph, we describe the postembryonic skeletal ontogeny of this ancient and unique monotypic lineage. The torrent-dwelling larva possesses a dorsoventrally flattened body and a head with tiny dorsal eyes, robust lower and upper jaw cartilages, well-developed trabecular horns, and a definable gap between the trabecular horns and the tip of the snout. Unlike tadpoles of many other frogs, those of Nasikabatrachus retain larval mouthparts into late metamorphic stages. This unusual feature enables the larvae to maintain their clinging habit until near the end of metamorphosis. The subsequent ontogenetic shift from clinging to digging is correlated with rapid morphological changes and behavioral modifications. Metamorphs are equipped with a shortened tibiafibula and ossified prehallical elements, which likely facilitate initial digging using the hind limbs. Subsequently, the frogs may shift to headfirst burrowing by using the wedge-shaped skull, anteriorly positioned pectoral girdle, well-developed humeral crests and spatula-shaped forelimbs. The transition from an aquatic life in torrents to a terrestrial life underground entails dramatic changes in skeletal morphology and function that represent an extreme in metamorphic remodeling. Our analysis enhances the scope for detailed comparative studies across anurans, a group renowned for the diversity of its life history strategies.